O exercício da autonomia negocial no teletrabalho : tecnologia e proteção jurídica - Battirola, Tálata Daiane Limberger (2024)
Work is inherent to human life. In this way, work is as old as man and, throughout history, it has been developed in the most different ways, in different contexts in terms of time and space, depending on different factors and, above all, with the influence of technological implementation. Thus, understanding the evolution based on the social and economic facts that have influenced the organization of work is of fundamental importance for the analysis of the law's response to the phenomena and tensions that involve the dynamics between the facts and values involved in the employment relationship, as well as with regard to the exercise of negotiating autonomy in the employment sphere. The aim of this study is to understand how to ensure legal protection for employees in a subordinate teleworking regime, in cases where the effectiveness of the heteronormative response in the protection of employment relationships is not observed, through the exercise of negotiating autonomy. In this sense, using the deductive method, through bibliographical and documentary review, indirect sources, as the basis of the investigative process, associated with legislative and jurisprudential analysis on the subject, as well as field interviews, through the oral history method, with a qualitative approach, it was realized that Labor Law cannot remain static in the face of the significant changes implied by technological innovations in productive relations. Furthermore, it was observed that the exercise of autonomy, as an ideal of human dignity, cannot be dissociated from the legal protection of workers and, in the case of teleworking, given the legislative gaps, it is an essential tool for resolving points not covered by the heteronomous standard, as a way of guaranteeing the protection of the interests and integrity of remote employees.